Economic integration and the optimal corporate tax structure with heterogeneous firms - Christian Bauer; Ronald B. Davies; Andreas Haufler (Center for Economic Studies and ifo Institute (CESifo), 2011)
We study the optimal combination of corporate tax rate and tax base in a model of a small open economy with heterogeneous firms. We show that it is optimal for the small country's government to effectively subsidize capital inputs by granting a tax allowance in excess of the true costs of capital. Economic integration reduces the optimal capital subsidy and drives low-productivity firms from the small country's home market, replacing them with high-productivity exporters from abroad. This endogenous policy response creates a selection effect that increases the average productivity of home firms when trade barriers fall, in addition to the well-known direct effects.
Keywords: H25; H87; F15; 330; corporate tax reform; trade liberalization; firm heterogeneity; Unternehmensbesteuerung; Steuerbemessung; Optimale Besteuerung; Kleines-offenes-Land; Außenhandelsliberalisierung; Wirtschaftsintegration; Produktivität; Theorie